The antecedents and outcome of leader voice-taking behavior: The mediating role of cognitive and affective factors - Li, Xu Zheng (2025)
The service sector has emerged as the driving force of China's economic growth, with the hotel industry relying on innovation for sustained development. As a labor-intensive industry, front-line employees (FLEs) are critical to service innovation. However, insufficient support from superiors, particularly their passive stance toward employees’ change-oriented voice, has led to high turnover among FLEs, thereby hindering consistent innovation. Strengthening the relationship between employee voice and leader voice-taking behavior (LVT) is essential for fostering service innovation. LVT, characterized by changeoriented and innovation-supportive leadership behavior, plays a pivotal role in facilitating employee-driven innovation. Grounded in persuasion theory, social information processing theory, and affective-events theory, this study investigates the antecedents and the outcomes of LVT in China’s hospitality sector. The research framework categorizes antecedents into three domains: message variables (promotive voice, prohibitive voice, issue importance, voice directness), source variables (employee expertise, voice efficacy, employee loyalty, value congruence), and contextual variables (diversity, leader-member exchange [LMX]). The study also explores the outcome of LVT, particularly employee service innovation, with cognitive factors such as felt obligation for constructive change (FOCC) and affective factors such as positive emotion and relational energy serving as mediators. Using a quantitative approach, the researcher collected data from FLEs in five-star international hotels in China through surveys using a two-stage sampling method. Of the 1,000 questionnaires distributed, 442 valid responses were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that LVT is positively influenced by promotive voice, issue importance, voice directness, employee loyalty, value congruence, diversity, and LMX, while prohibitive voice negatively affects it. Employee expertise and voice efficacy showed no significant impact. LVT is positively correlated with FOCC, positive emotion, relational energy, and service innovation. The mediating effects of FOCC (as cognitive factor) and positive emotion and relational energy (as affective factors) are also confirmed. Additionally, the Direct Voice Mechanism moderates the relationships between LVT and variables such as prohibitive voice, issue importance, LMX, and employee loyalty. This study offers valuable insights into how LVT influences service innovation in the high-turnover hospitality industry and highlights practical strategies for enhancing front-line employees’ innovation through supportive leadership and management practices.